Pola Komunikasi Dosen Dalam Menanggulangi Kejenuhan Belajar Mahasiswa - Fiqhan Muslim, Ibnu; Salsabila, Fahmi (Edu Sosial, 2023)
Many factors contribute to student learning boredom, but specifically the learning boredom experienced is related to time management, interaction with lecturers, adjustment to the campus environment, and lack of support. These are the things that most often and often trigger students to experience learning boredom. There are several methods to prevent and overcome learning boredom, one of which is by implementing good communication patterns for lecturers towards their students. Communication must be two-way, meaning that communication must be built with a response from the communicants, in this case between the lecturer and the students. . The method used in this research uses a qualitative approach. Communication patterns are closely related to the process of a lecturer's approach to students, of course each lecturer has a certain strategy in communicating. Several things that a lecturer can do to overcome students who experience learning boredom include improving teaching communication patterns. Lecturers need to package learning communication patterns to make them more interesting and enjoyable. To create creative, responsive and fun learning, of course it must be supported by students, parents and the community.